2013
DOI: 10.1093/rheumatology/kes388
|View full text |Cite
|
Sign up to set email alerts
|

GAPSS: the Global Anti-Phospholipid Syndrome Score

Abstract: These data propose a substantial improvement in risk prediction of thrombosis or PL in SLE based on assessment of the GAPSS, a quantitative scoring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
188
4
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(227 citation statements)
references
References 22 publications
7
188
4
10
Order By: Relevance
“…The APS-Score [18,19] and GAPPSS [20] showed that multiple positivity for aPL will increase the thrombotic risk. Testing aPS/PT would be useful for the prediction of the thrombotic risk in patients with APS.…”
Section: Discussionmentioning
confidence: 99%
“…The APS-Score [18,19] and GAPPSS [20] showed that multiple positivity for aPL will increase the thrombotic risk. Testing aPS/PT would be useful for the prediction of the thrombotic risk in patients with APS.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study we have reported that aPS/PT of IgG and IgM isotype are strongly associated with adverse pregnancy outcome, irrespective of other antiphospholipid antibodies [22], and that their detection is particularly important for evaluation of obstetric APS. However in the present study, we show that IgA aPS/PT (differently from IgG and IgM) were not found more prevalently in women with pregnancy complications.…”
Section: Discussionmentioning
confidence: 96%
“…In the last decade, antibodies against prothrombin, specifically aPS/PT were recognized to be importantly associated with clinical manifestations of APS [20][21][22][23]28]. In our previous study we have reported that aPS/PT of IgG and IgM isotype are strongly associated with adverse pregnancy outcome, irrespective of other antiphospholipid antibodies [22], and that their detection is particularly important for evaluation of obstetric APS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters and scores included in GAPSS are hyperlipidemia (score 3), arterial hypertension (score 1), IgG/IgM aCL (score 5), IgG/IgM ab 2 GPI (score 4), IgG/IgM antiphosphatidyl serine (aPS)/anti prothrombin (score 3), and LAC (score 4). A GAPSS value of C10 or C11 was reported to have the best diagnostic accuracy for thrombosis or pregnancy loss [34][35][36].…”
Section: Risk Of Thrombosis Assessment-global Antiphospholipid Score mentioning
confidence: 99%